Enhancement of Students’ Artistic Talents through Formation of Projective-Research Knowledge, Skills and Abilities - Sharofovna, Artikova Ozoda; Kholmatovich, Alkarov Kodir; Ravshanovna, 3Abdulakhadova Shokhida; Melievna, Oripova Feruza; Khatamovich, Tugalov Ismatjon (International Journal of Psychosocial Rehabilitation, 2020)
in this article, the advantages of fulfil the projective-researching performance while arranging creational upbringing in a comprehensive-secondary institution.